2021
DOI: 10.1055/a-1667-6624
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercise Training on Plasma Volume Variations: A Systematic Review

Abstract: The aim of this systematic review was to summarize the evidence on the acute and long-term effects of exercise training on PV, in both trained and untrained individuals and to examine associations between changes in %PVV and change in physical/physiological performance. Despite the status of participants and the exercise duration or intensity, all the acute studies reported a significant decrease of PV (effect size: 0.85<d<3.45, very large), and ranged between 7% and 19.9%. In untrained individuals, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 98 publications
2
10
0
Order By: Relevance
“…Another indicator of differences in exercise stress, despite the identical total work, is PVC. Even though the exercise-induced hemoconcentration is multifactorial, 49 intensity seems to be important 50 ; in agreement with this, all HIIE trials presented higher PVC than CON. However, the reduction in plasma volume was greater in HIIE60 than in the other HIIE trials, reflecting greater exercise stress-related changes, similar to those observed after a 30-s sprint.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Another indicator of differences in exercise stress, despite the identical total work, is PVC. Even though the exercise-induced hemoconcentration is multifactorial, 49 intensity seems to be important 50 ; in agreement with this, all HIIE trials presented higher PVC than CON. However, the reduction in plasma volume was greater in HIIE60 than in the other HIIE trials, reflecting greater exercise stress-related changes, similar to those observed after a 30-s sprint.…”
Section: Discussionsupporting
confidence: 80%
“…However, the reduction in plasma volume was greater in HIIE60 than in the other HIIE trials, reflecting greater exercise stress-related changes, similar to those observed after a 30-s sprint. 51 , 52 The large decrease in plasma volume during HIIE60 may be attributed to both hemodynamic (i.e., increase in blood pressure) and osmotic changes in working muscles (e.g., from lactate increase), 31 , 50 , 51 which are both indicative of the magnitude of exercise stress.…”
Section: Discussionmentioning
confidence: 99%
“…In order to optimize physical performance, previous studies are interested to control level of plasma volume among soccer players in response to the training (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the systematic literature review of Zouhal et al (9) suggests that long-term exercise training can also induce a significant increase of plasma volume (PV) in healthy untrained individuals. More specify, Kanstrup et al (11) observed that oxygen transport and VO 2max are linked to blood volume and hemoglobin (Hb) concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation